A new curcumin analog, CCA-1.1, induces cell death and cell cycle arrest in WiDr colon cancer cells via ROS generation - Febri Wulandari, Muthi Ikawati&, Mitsunori Kirihata, Jun-Ya Kato, Edy Meiyanto& (Journal of Applied Pharmaceutical Science, 2021)
The new Pentagamavunone-1 (PGV-1) derivative, chemoprevention-curcumin analog 1.1 (CCA-1.1), is described as an improved physicochemical feature with similar cytotoxic activity on colon cancer cells and binding interaction to various cancer biomarkers. The current study explored the cytotoxic activity related to its ability to promote physiological changes in the WiDr colon cancer cell line. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was used to assess the cell viability of WiDr and NIH-3T3 cells on the treatment of CCA-1.1 and PGV-1. 2′,7′-dichlorofluorescein diacetate staining, propidium iodide staining, and annexin V-PI staining were conducted to examine reactive oxygen species (ROS) level, cell cycle profiles, and apoptosis, respectively. For more examination on morphological changes, the SA-β-gal staining was used to detect senescence occurrence. We retrieved a more significant cytotoxic effect on WiDr by CCA-1.1 than PGV-1 and no effect on NIH-3T3 fibroblast cells. Our compound stimulated the arrest of the cell cycle at the G2/M phase, apoptosis, ROS generation, and senescence at an equal level to PGV-1. Altogether, these data reinforce CCA-1.1 as a viable alternative to PGV-1, attributed to its improved physicochemical features that are beneficial in designing dosage formulations for medical purposes.
Keywords: CCA-1.1, colon cancer, cytotoxic, cell cycle, apoptosis, ROS